1991
DOI: 10.1002/ijc.2910490504
|View full text |Cite
|
Sign up to set email alerts
|

Association of C‐erbB‐2 protein over‐expression with high rate of cell proliferation, increased risk of visceral metastasis and poor long‐term survival in breast cancer

Abstract: c-erbB-2 protein over-expression was studied immunohistochemically in 319 paraffin-embedded breast carcinomas representing 89% of all breast-cancer cases operated in the Tampere University Hospital between 1977 and 1981. The immunohistochemical evaluation of c-erbB-2 was optimized using protease pre-treatment and verified using antibodies for both the external and the internal domains of the protein. c-erbB-2 over-expression was found in 72 (23%) of the 319 cases and was associated with high histological and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
129
4
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(154 citation statements)
references
References 26 publications
16
129
4
5
Order By: Relevance
“…9 Basal-like and HER2-positive tumors are more likely to metastasize to the brain, and they have the worst prognosis. 10 Without being able to perform gene expression profiling, we have defined subsets of patients based on the expression of ER, PgR, and HER2 receptors, which were proposed by Hugh et al 11 Metastatic pattern and propensity of biological subtypes to the brain, observed in our study, were discussed elsewhere. 6 We have observed a good response to hormonal therapy in the luminal A patient subset and to chemotherapy with targeted therapy in the HER2-positive breast cancer patients (those with HER2 and luminal B subtypes).…”
Section: Discussionmentioning
confidence: 96%
“…9 Basal-like and HER2-positive tumors are more likely to metastasize to the brain, and they have the worst prognosis. 10 Without being able to perform gene expression profiling, we have defined subsets of patients based on the expression of ER, PgR, and HER2 receptors, which were proposed by Hugh et al 11 Metastatic pattern and propensity of biological subtypes to the brain, observed in our study, were discussed elsewhere. 6 We have observed a good response to hormonal therapy in the luminal A patient subset and to chemotherapy with targeted therapy in the HER2-positive breast cancer patients (those with HER2 and luminal B subtypes).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies demonstrated increased risk of brain relapse in breast cancer patients with overexpressed or amplified HER2-neu gene [5][6][7][8]. HER2 abnormalities occur in 20-30% of invasive breast cancers and are associated with more aggressive tumor growth, increased risk of relapse and shorter survival [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The normal human HER-2/ neu proto-oncogene is frequently ampli®ed or overexpressed in many types of human cancers. HER-2/neu overexpression correlates with tumor grade, size, relapse rate, lymph node and visceral metastases in breast cancer patients and decreased disease-free survival in breast, ovary, lung, stomach and salivary gland cancers (Slamon et al, 1987;Borg et al, 1990;Paterson et al, 1991;Kallioniemi et al, 1991;Press et al, 1993Press et al, , 1994Berchuck et al, 1990;Kern et al, 1990;Yonemura et al, 1991). Transgenic mice carrying mutation-activated HER-2/neu, or overexpressing normal HER-2/neu, induce mammary adenocarinoma with a high frequency of metastasis (Muller et al, 1988;Bouchard et al, 1989;Guy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%